Feasibility Study of Polygeneration Turbine Plants Based on Carbon Dioxide - A. V. Ovsyannik; V. P. Kliuchinski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2023)
Schemes of polygeneration plants based on carbon dioxide are presented, in which the energy source are secondary energy resources and a gas turbine plant. These polygeneration schemes make it possible to simultaneously produce electricity, heat, cold, carbon dioxide in liquid and gaseous aggregate state, as well as to dispose of part of the carbon dioxide emitted into the atmosphere, due to its absorption from combustion products and use for commercial and technological purposes. The structure of the mathematical model of the program that has been developed for the exergetic analysis of polygeneration schemes is presented. With the help of the program, an exergetic analysis of polygeneration schemes was performed, in which polygeneration turbine units with different parameters of carbon dioxide in front of the turbine, as well as single and double overheating of carbon dioxide were compared. The exergetic electrical efficiency of polygeneration plants as a whole and its individual elements were taken as the criteria to be compared. Polygeneration plants with double overheating and supercritical parameters of carbon dioxide in front of the turbine have the greatest efficiency. A method for calculating of the economic indicators of polygeneration schemes is presented, which makes it possible to take into account the influence of double overheating and carbon dioxide parameters in the cost of a polygeneration plant. The economic efficiency indicators of various versions of polygeneration schemes, such as the internal rate of return, net discounted income, static and dynamic payback periods are obtained. It has been established that all variants of polygeneration schemes have acceptable indicators of economic efficiency, the static payback period of the proposed polygeneration schemes does not exceed 5 years, while the internal rate of return does not decrease by less than 22,8%.